Myocardial protection following del Nido cardioplegia in pediatric cardiac surgery. (May 2018) - Panigrahi, Debasish; Roychowdhury, Saibal; Guhabiswas, Rahul; Rupert, Emmanuel; Das, Mrinalendu; Narayan, Pradeep
Background: This study was designed to compare myocardial protection with del Nido cardioplegia and conventional blood cardioplegia in children undergoing cardiac surgery in Risk Adjustment for Congenital Heart Surgery categories 1 and 2. Methods: Sixty patients were randomized into 2 groups receiving del Nido cardioplegia solution or conventional blood cardioplegia. Myocardial injury was assessed using biochemical markers (troponin I and creatine kinase-MB). Vasoactive-inotropic scores were calculated to compare inotropic requirements. Results: Demographic characteristics, cardiopulmonary bypass time, and aortic crossclamp time were comparable in the 2 groups. Time-related changes in troponin I and creatine kinase-MB were similar in both groups. Statistically significant differences were seen in total cardioplegia volume requirement ( p < 0.0001), number of cardioplegia doses given ( p < 0.0001), packed red cell volume usage during cardiopulmonary bypass ( p < 0.02), and time taken to restore spontaneous regular rhythm ( p < 0.0001). Vasoactive-inotropic scores on transfer to the intensive care unit ( p < 0.040) and at 24 h ( p < 0.030) were significantly lower in the del Nido group. Duration of mechanical ventilation, intensive care unit stay, and hospital stay were comparable in the 2 groups. Conclusions: Our results show that del Nido cardioplegia solution is as safe as conventional blood cardioplegia. Moreover, it provides the benefits of reduced dose requirement, lower consumption of allogenic blood on cardiopulmonary bypass, quicker resumption of spontaneous regular cardiac rhythm, and less inotropic support requirement on transfer to the intensive care unit and at 24 h, compared to conventional blood cardioplegia.